Sociological theory and criminological research views from Europe and the United States - Deflem, Mathieu (Amsterdam ; Oxford : Elsevier JAI, 2006)
The contributions in this volume highlight the value of sociological theorizing in various strands of criminological research. The chapters present concrete analyses and discussions of how sociological theory has been useful to the respective authors efforts in criminological research. Collectively, they aim to show that some of the very best criminological work is informed in useful and varied ways by sociological theory. Revealing the global reach and nationally distinct variations in the practice of sociological theory and criminology, this volume is explicitly trans-Atlantic in terms of its contributors and the topics and theories they discuss. This book offers ten informative chapters as well as two commentaries, written by some of the leading practitioners of criminological theory and research today. Among the theoretical traditions discussed in this book are a range of perspectives, including macro and micro models as well as theories of criminal behavior and perspectives of social control. The empirical aspects of crime and criminal justice to which these theories are applied are likewise varied and, importantly, drawn from concrete socio-historical settings in multiple nations. The chapters reveal the breadth and depth of criminological sociology in its explicit and informed reliance on insights from sociological theory. This title discusses the usefulness of sociological theory in criminological research. It includes international contributors for a multinational perspective.
Description based on print version record.
Keywords: Crime -- Sociological aspects; Crime & criminology; Social Science -- Criminology